Aerobic exercise promotes executive functions and impacts functional neural activity among older adults with vascular cognitive impairment. Issue 3 (21st April 2017) - Hsu, Chun Liang; Best, John R; Davis, Jennifer C; Nagamatsu, Lindsay S; Wang, Shirley; Boyd, Lara A; Hsiung, GY Robin; Voss, Michelle W; Eng, Janice Jennifer; Liu-Ambrose, Teresa
Abstract : Background: Vascular cognitive impairment (VCI) results from cerebrovascular disease, and worldwide, it is the second most common type of cognitive dysfunction. While targeted aerobic training is a promising approach to delay the progression of VCI by reducing cardiometabolic risk factors, few randomised controlled trials to date have specifically assessed the efficacy of aerobic training on cognitive and brain outcomes in this group at risk for functional decline. Aim: To examine the effect of moderate-intensity aerobic training on executive functions and functional neural activity among older adults with mild subcortical ischaemic VCI (SIVCI). Methods: Older adults with mild SIVCI were randomly assigned to: (1) 6-month, 3×/week aerobic training (n=10) or (2) usual care (control; n=11). Participants completed functional MRI (fMRI) at baseline and trial completion. During the fMRI sessions, behavioural performance on the Eriksen flanker task and task-evoked neural activity were assessed. Results: At trial completion, after adjusting for baseline general cognition, total white matter lesion volume and flanker performance, compared with the control group, the aerobic training group significantly improved flanker task reaction time. Moreover, compared with the controls, the aerobic training group demonstrated reduced activation in the left lateral occipital cortex and right superior temporal gyrus. Reduced activity in these brain regions was significantly associated with improved (ie, faster) flanker task performance at trial completion. Summary: Aerobic training among older adults with mild SIVCI can improve executive functions and neural efficiency of associated brain areas. Future studies with greater sample size should be completed to replicate and extend these findings.